The role of homogenization cycles and Poloxamer 188 on the quality of mitochondria isolated for use in mitochondrial transplantation therapy - Ryosuke Takegawa; Kei Hayashida; Atsushi Murao; Yusuke Endo; Cyrus E. Kuschner; Jacob Kazmi; Eriko Nakamura; Ping Wang; Lance B. Becker (Scientific Reports)
Abstract Mitochondrial transplantation (MTx) offers a promising therapeutic approach to mitigate mitochondrial dysfunction in conditions such as ischemia–reperfusion (IR) injury. The quality and viability of donor mitochondria are critical to MTx success, necessitating the optimization of isolation protocols. This study aimed to assess a rapid mitochondrial isolation method, examine the relationship between mitochondrial size and membrane potential, and evaluate the potential benefits of Poloxamer 188 (P-188) in improving mitochondrial quality during the isolation process. Mitochondria were isolated from pectoral muscle biopsies of adult male Sprague–Dawley rats using an automated homogenizer. MitoTracker Deep Red (MTDR) staining and flow cytometry were used to assess mitochondrial purity, while the JC-1 assay evaluated membrane potential. Mitochondrial size groups were compared for membrane potential differences. Homogenization frequency and P-188 supplementation (1 mM) were assessed for their effects on mitochondrial membrane potential and particle size, and particle counts. The rapid isolation method yielded mitochondria that retained sufficient membrane potential to be effectively inhibited by carbonyl cyanide 3-chlorophenylhydrazone (CCCP), a disruptor of mitochondrial membrane potential. Larger mitochondria exhibited significantly higher JC-1 ratios, indicating greater membrane potential. Excessive homogenization (10 cycles) reduced membrane potential compared to 3 cycles homogenization (P = 0.026). P-188 significantly increased the JC-1 ratio from 10.26 ± 2.57 to 33.78 ± 17.78 (P = 0.023). Particle size and count analysis revealed that 10 cycles homogenization significantly increased particle count compared to 3 cycles homogenization (P = 0.0001), but was associated with smaller particle sizes (P = 0.0031). The rapid mitochondrial isolation method produced viable mitochondria, with larger mitochondria exhibiting superior membrane potential. Reducing homogenization frequency and incorporating P-188 improved mitochondrial quality and preserved particle size. These strategies offer promising strategies for optimizing MTx protocols. Further refinement of these techniques is necessary for their clinical application in MTx therapy.